Transient performance of a solar humidification–dehumidification desalination system based on hollow fiber membrane. Issue 3 (13th May 2021) - Zhang, Ning; Yin, Shao-You; Vafai, Kambiz
Abstract: Solar humidification–dehumidification desalination system based on hollow fiber membrane is a promising method to produce drinkable water from brine due to its abilities for low primary energy consumption and pollution prevention for the liquid seawater droplets. As operating conditions change with temporal weather conditions, a dynamic model of this desalination system is developed and experimentally validated in this study. Transient performance is investigated and a regulation strategy is proposed. It is found that the startup time can be reduced substantially by decreasing the mean pore diameter, porosity of the membrane, solar collector area, and volume of the seawater in the storage tank, and increasing the packing fractions of the humidifier. The specific freshwater production (SWP) rate at the equilibrium state grows with longer mean pore diameter, higher porosity of the membrane, more solar collector areas, and less packing fractions of the humidifier. SWP is basically constant with different volumes of the seawater in the storage tank. Variations of solar radiation cause the low freshwater production and high energy consumption especially in the morning and afternoon. Utilizing our model, the hour-by-hour adjustment is also established. The accumulated water production in 1 day can be increased by 13.5% and the energy consumption can decrease by over 23% based on decreasing flow rates of the seawater in the morning and increasing flow rates of the cooling water in the afternoon. The proposed dynamic model will be helpful for the daily regulation of the seawater desalination system and a better performance can be realized. Graphical Abstract: